ANALISIS FIQH SIYASAH TERHADAP PERAN DEWAN PERWAKILAN RAKYAT DALAM HUKUM TATA NEGARA INDONESIA - Muhammad Raka Mahendra; Paisol Burlian; Yuswalina Yuswalina (Universitas Islam Negeri Raden Fatah Palembang, 2021)
Abstract In the state government system there is a legislature as a channel for the aspirations of the people. In the Indonesian government it is known as the People's Representative Council (DPR), while in Islamic government it is known as Ahlu Al-Halli Wa Al-Aqdi. Prior to the reform, the role of the DPR in Indonesia had not been implementbased on the 1945 Constitution. However, after the reform the role of the DPR has been running well after the amendment of the 1945 Constitution. Indonesian country?; (2) What is the role of the House of Representatives (Ahlu Al-Halli Wa Al-Aqdi) in Fiqh Siyasah?; and (3) What are the similarities and differences in the roles of the House of Representatives and Ahlu Al-Halli Wa Al-Aqdi in Indonesian Constitutional Law and Fiqh Siyasah?. Normative juridical study or what is known as library research is used in this research with comparative descriptive nature using normative methods where the author analyzes one source of data, namely secondary data, which means the data is sorted into a primary, secondary and also tertiary law. Reffering on the results obtained, the role of the DPR to oversee the running of the government, form laws, and provide considerations concerning the people. While the role of “Ahlu Al-Halli Wa Al-Aqdi”is to elect and dismiss the head of state, make legal regulations and consult to resolve the problems of his people. Thus, we concludefrom this research is that these two institutions have many similarities in carrying out their roles in the government system, and both also have several differences that can be seen from: (a) Their position in government; (b) How to elect and inaugurate the head of state; (c) Carry out their duties in government; (d) The system in government; and (e) In its membership in the government. Keywords: Legislative Institutions, Role, Constitutional Law, Fiqh Siyasah